2011
DOI: 10.1007/s10571-011-9687-0
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Nuclear-sorted Caspase-12 Fragments in Cerebral Cortical and Hippocampal Neurons in Rats Damaged by Autologous Blood Clot Embolic Brain Infarctions

Abstract: Following endoplasmic reticulum (ER) stress, cerebral infarctions have been reported to involve an apoptotic process, including the activation of the caspase cascade. To confirm whether fragmented caspase-12, which is activated by cleavage and is detectable during ER stress, is also involved in embolic cerebral infarctions in rats, we adopted an autologous blood clot model for the analysis of cerebral infarctions. We performed experiments in rats with brain infarctions, which are closely related to embolic cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…The processing of caspase-12 is at the N-terminal region, either by caspases or by calpains (10). Similar to this study, Shimoke et al found translocated caspase-12 in nuclei in cortical and hippocampal neurons in the case of an experimental blood clot model (38). We particularly found nuclear immunreactivity of caspase-12 in the radiation group in our study.…”
Section: █ Acknowledgementsupporting
confidence: 90%
“…The processing of caspase-12 is at the N-terminal region, either by caspases or by calpains (10). Similar to this study, Shimoke et al found translocated caspase-12 in nuclei in cortical and hippocampal neurons in the case of an experimental blood clot model (38). We particularly found nuclear immunreactivity of caspase-12 in the radiation group in our study.…”
Section: █ Acknowledgementsupporting
confidence: 90%
“…International Publisher activation of caspase-3 and ERS-induced cell apoptosis in astrocytes following ischemic stroke [5][6][7]. Caspase-12 is classified in the group I family of caspases, which are characterized as inflammatory caspases [8,9].…”
Section: Ivyspringmentioning
confidence: 99%
“…Accordingly, in their active form, UPR transducers serve as ER stress markers. Critically, cumulative evidence suggests that all three signalling arms of the UPR are activated following ischemia [28,[60][61][62][63][64][65][66][67][68][69][70][71] .…”
Section: Er Response To Ischemiamentioning
confidence: 99%